Mapping the Fit Between Research and Multimedia: A podcast exploration of the place of multimedia within / as scholarship - Riecken, Ted (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
Using the medium of the podcast this piece highlights key factors that may have an impact on how multimedia is used by educational researchers. The author examines the degree of congruence between the prevailing norms of representation in educational research and the norms and processes of multimedia as a way of presenting knowledge and information. The podcast also explores the extent to which multimedia is a usable resource in schools, and whether the skill sets and inquiry processes of educational researchers are compatible with the rip / burn / remix manifestos of multimedia and maker cultures. The author / podcaster concludes that changes in the adoption and use of multimedia within / as scholarship will evolve over time as more and more individuals learn how to produce multimedia content, while at the same time, consumers of educational research are becoming acclimatized to increased diversity in forms of knowledge representation.